2013
DOI: 10.1186/1746-4811-9-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel system for in situ determination of heat tolerance of plants: first results on alpine dwarf shrubs

Abstract: BackgroundHeat stress and heat damage to plants gain globally increasing importance for crop production and plant survival in endangered habitats. Therefore the knowledge of heat tolerance of plants is of great interest. As many heat tolerance measurement procedures require detachment of plants and protocols expose samples to various heat temperatures in darkness, the ecological relevance of such results may be doubted. To overcome these constraints we designed a novel field compatible Heat Tolerance Testing S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…These results are in agreement with a recent methodological study by Buchner et al (2013). By means of a visual estimation of leaf damage in two alpine dwarf shrub species, the authors observed significant increases in the lethal temperature when heat treatment was done on attached leaves in situ under natural solar irradiance as compared with darkness.…”
Section: Discussionsupporting
confidence: 82%
“…These results are in agreement with a recent methodological study by Buchner et al (2013). By means of a visual estimation of leaf damage in two alpine dwarf shrub species, the authors observed significant increases in the lethal temperature when heat treatment was done on attached leaves in situ under natural solar irradiance as compared with darkness.…”
Section: Discussionsupporting
confidence: 82%
“…Small thermocouple sensors (Type T; TT‐Ti‐36, Omega Engineering Inc.; solder junction diameter: 0.3 mm) were used to measure leaf temperature and were placed on the lower leaf surface with special leaf clamps to allow unrestricted solar irradiation and leaf transpiration (see Buchner et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…The growth chamber did not have the capability to adjust light levels. Although light can influence chlorophyll fluorescence (Buchner, Karadar, Bauer, & Neuner, 2013; Ludlow, 1987), we assumed that the low light levels for the 45‐min or 90‐min treatment duration did not substantially influence results. Photosynthesis, chlorophyll fluorescence, and foliar NSC content were monitored in control and treated plants prior to treatment (day 0) and 2, 15, 25, and 50 days after treatment.…”
Section: Methodsmentioning
confidence: 99%